2000
DOI: 10.1902/jop.2000.71.9.1425
|View full text |Cite
|
Sign up to set email alerts
|

The Fcγ Receptor Genotype as a Risk Factor for Generalized Early‐Onset Periodontitis in Japanese Patients

Abstract: This study indicates that the FcgammaRIIIb-NA2 allele and possibly FcgammaRIIIa-158F could be associated with susceptibility to G-EOP in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 59 publications
9
71
1
1
Order By: Relevance
“…The distribution observed was similar to that in previous reports of the Japanese population (allelic frequency of FCGR3A-158F was 0.72-0.74; refs. 31,32). The distribution of FCGR3A genotype among various subgroups based on clinical backgrounds is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution observed was similar to that in previous reports of the Japanese population (allelic frequency of FCGR3A-158F was 0.72-0.74; refs. 31,32). The distribution of FCGR3A genotype among various subgroups based on clinical backgrounds is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FcgRIIIB-NA2 allele was also associated with the onset of AGP, which is consistent with our previous results. 21 The haplotype formed by FcgRIIBÀ232T and FcgRIIIB-NA2 did not exist in controls, suggesting a weak but significant positive linkage disequilibrium between FcgRIIBÀ232I and FcgRIIIB-NA2, whereas 232I-NA1 was the most common haplotype in controls and patients. Additionally, in AGP patients, the FcgRIIBÀ232T allele formed a haplotype with the FcgRIIIB-NA2 allele (the estimated haplotype frequency of the 232T-NA2 was 14.8%).…”
Section: Discussionmentioning
confidence: 98%
“…8,9 In Japanese patients, FcγRIIIb NA2 allele was associated with Generalized (G)-EOP 17 and was found more often in adult periodontitis with disease recurrence. 29 The combined carriage rate of both FcγRIIIb NA2 and FcγRIIIa-158F gene was more frequently detected in G-EOP over healthy controls.…”
Section: Distribution Of Fcγriii Genotypes and Allelesmentioning
confidence: 99%
“…29 The combined carriage rate of both FcγRIIIb NA2 and FcγRIIIa-158F gene was more frequently detected in G-EOP over healthy controls. 17 In African Americans, an association between the FcγRIIIb and localized AgP has been found. 16 However, In this study, no significant association was observed between the FcγRIIIb polymorphism and AgP.…”
Section: Distribution Of Fcγriii Genotypes and Allelesmentioning
confidence: 99%